Quality of Public Universities and Graduates’ Employability in Malaysia: The Mediating Role of Graduates’ Competencies - Amal Ahmad Almasri, Noor Azman Ali, Amer Hamzah Jantan, Mass Hareeza Ali (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to investigate how graduates’ competencies mediate on the relationship between the quality of public universities and graduates’ employability. This study also investigates the direct effect between the quality of public universities, graduates’ competencies and graduates’ employability. The study focused on graduates from public universities in Malaysia. A questionnaire survey administered to 570 graduates from three public universities (Universiti Putra Malaysia, Universiti Kebangsaan Malaysia and University of Malaya) was analyzed using the structural equation modelling technique for estimating the effects among the variables studied. The findings confirmed the direct effect between variables. The results also indicate that graduates’ competencies show a partial mediating role in the relationship between the quality of public universities and graduates’ employability. In addition, the findings imply that any effort to enhance the competencies of public universities’ graduates can help them to be more employable in the labour market. This study also provides a framework and understanding of how the quality of public universities and graduates’ competencies relate to graduates’ employability in one model. Therefore, this study recommends that public universities focus more on the continuation of quality improvement and graduates’ competencies. Keywords: university quality; graduate, competencies, employability, structural equation modeling.